Biocompatible conjugation of Tris base to 2-acetyl and 2-formyl phenylboronic acid. Issue 24 (30th May 2019) - Li, Kaicheng; Kelly, Michael A.; Gao, Jianmin
Abstract : Tris, a commonly used buffering agent, readily reacts with 2-acetyl/formyl phenylboronic acid in complex biological media, yielding conjugates with kinetic stability similar to oximes. Abstract : We describe the biocompatible conjugation of the Tris base to 2-formyl and 2-acetylphenylboronic acid (abbreviated as 2-FPBA and 2-APBA respectively), which have emerged as a versatile chemotype for fast biocompatible conjugation reactions. Tris base was found to react with 2-FPBA/APBA to give oxazolidinoboronate (OzB) complexes, analogous to the thiazolidinoboronate (TzB) and imidazolidinoboronate (IzB) complex formation that we recently reported. The Tris conjugations proceed well in complex biological media, and in contrast to the TzB/IzB complexes, the Tris conjugates exhibit superior kinetic stability (dissociation over days) as well as chemical stability against oxidation. We demonstrate the utility of such conjugation chemistries via a small molecule-induced peptide cyclization in blood serum.